Performance and carcass quality of Czech Fleckvieh, Charolais and Charolais × Czech Fleckvieh bulls fed diets based on different types of silages - L. Bartoň; V. Kudrna; D. Bureš; R. Zahrádková; V. Teslík (Czech Journal of Animal Science, 2007)
A total of thirty-four Czech Fleckvieh (CF), Charolais (CH) and Charolais × Czech Fleckvieh (CH × CF) bulls with an average weight of 284 kg were included in the experiment and fed ad libitum two mixed diets: MS (based on maize silage) and LCS (based on legume-cereal and lucerne silages) with different concentrations of dietary energy until slaughter at the target live weight of 600 kg. The CF bulls consumed more dry matter (DM) of feed daily than the CH bulls (P < 0.05) and gained weight less efficiently than the CH × CF and CH animals (P < 0.01) during the entire experiment. The killing-out percentage was lower in the CF than in the CH × CF and CH (P < 0.05). The CH bulls received a higher score for carcass conformation and a lower score for carcass fatness (P < 0.01) than the CF bulls, had lower proportions of kidney and cod fat (P < 0.01) than the CH × CF and CF bulls, and produced the highest percentage of high-priced meat (P < 0.05) and the lowest percentage of separable fat (P < 0.001). The bulls on the MS diet were younger than the others at the end of the experiment (P < 0.01), gained weight more rapidly (P < 0.001), consumed less DM (P < 0.001) daily, utilized nutrients more efficiently over the entire experimental period (P < 0.001), and had a higher proportion of internal fat than the LCS bulls. It can be concluded that purebred CH bulls were superior to the other breed groups in most of the traits observed. The intensive diet based on maize silage increased average daily gains, reduced the time needed to achieve the target slaughter weight, and improved the feed efficiency of bulls.